2022
DOI: 10.29062/edu.v6i2.427
|View full text |Cite
|
Sign up to set email alerts
|

The Students’ Perception toward Learning Platform of Quizizz in Learning Vocabularies at MAN 1 Malang

Abstract: The education system in Indonesia has been impacted by the spread of Covid-19. Learning occurs not only in real objects but also in cyberspace, such as through internet intermediaries. This requires the adaptation and sustainability of the teaching-learning process at all levels of guidance. Online learning has been designated as a distance learning management system by the Indonesian government. The sample of this research was 89 sample of the eleventh-grade students of Madrasah Aliyah Negeri I of Kabupaten M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…They have difficulty pronouncing the vocabulary because they are used to pronouncing the Indonesian alphabet. Students experience difficulties and fear in vocabulary because English is a foreign language for them, and they lack motivation (Albadri et al, 2022).…”
Section: The Challenges Of Animaker As Learning Mediamentioning
confidence: 99%
“…They have difficulty pronouncing the vocabulary because they are used to pronouncing the Indonesian alphabet. Students experience difficulties and fear in vocabulary because English is a foreign language for them, and they lack motivation (Albadri et al, 2022).…”
Section: The Challenges Of Animaker As Learning Mediamentioning
confidence: 99%
“…Learning objectives will be satisfied if adequate learning approaches for the development of information and communication technology are available (Handoko et al, 2021) Students should found the process of teaching and learning English in an EFL class to be meaningful and entertaining. A problem for ELT teachers was determining how the teacher and materials can provide an engaging learning environment in the classroom, Singh and Richards (2006) in Albadri et al, (2022). Educators and students collaborated to discover solutions to these problems (Maming et al, 2022).…”
Section: Introductionmentioning
confidence: 99%